ANALISIS FAKTOR-FAKTOR MOTIVASI KERJA PEGAWAI DI PUSKESMAS PAAL V KECAMATAN KOTA BARU JAMBI - Andri Saputra (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2015)
The purpose of this study was to describe the factors of employee motivation at the Paal V Health Center, Kota Baru Jambi, and to analyze the factors of employee motivation at the Paal V Health Center, Kota Baru, Jambi. The research method used in this study was descriptive qualitative analysis and data collection was carried out through literature, interviews, and through questionnaires. Respondents in this study were employees of the Paal V Health Center, Kota Baru, Jambi. The results of this study indicate that: the overall average of the work motivation factors of the employees of the Paal V Health Center, Kota Baru Jambi, is that the employees are considered motivated. Based on the results of this study, it is recommended that the fulfillment of work motivation factors provided by the Paal V Health Center in Kota Baru Jambi to its employees must be maintained and further enhanced in terms of fulfilling physiological needs, safety and security needs, social needs, so that the work motivation of employees increases. get very motivated. There needs to be attention from the leadership to appreciate the results of the work of employees by giving praise or appreciation to employees whose work performance is good so that employees feel valued for the results of their work. Leaders must provide more opportunities for employees to develop their potential through education and training so that the abilities of employees will increase.